2011
DOI: 10.1016/j.biomaterials.2011.07.056
|View full text |Cite
|
Sign up to set email alerts
|

Changes of chondrocyte expression profiles in human MSC aggregates in the presence of PEG microspheres and TGF-β3

Abstract: Biomaterial microparticles are commonly utilized as growth factor delivery vehicles to induce chondrogenic differentiation of mesenchymal stem/stromal cells (MSCs). To address whether the presence of microparticles could themselves affect differentiation of MSCs, a 3D co-aggregate system was developed containing an equal volume of human primary bone marrow-derived MSCs and non-degradable RGD-conjugated poly(ethylene glycol) microspheres (PEG-μs). Following TGF-β3 induction, differences in cell phenotype, gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
46
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 53 publications
2
46
0
Order By: Relevance
“…21,22 To regulate the release of factors, loading microparticle containing factors into the scaffolds 23 and covalently binding the factors to the scaffolds have been used in recent research of chondrogenesis. 24,25 However, the effect of microspheres themselves on cell differentiation and covalent binding on the activity of factors cannot be well controlled, so both methods do not mimic the natural presentation of the factors in vitro. 26 In addition, the preparation of these controlled release systems is relatively complicated.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 To regulate the release of factors, loading microparticle containing factors into the scaffolds 23 and covalently binding the factors to the scaffolds have been used in recent research of chondrogenesis. 24,25 However, the effect of microspheres themselves on cell differentiation and covalent binding on the activity of factors cannot be well controlled, so both methods do not mimic the natural presentation of the factors in vitro. 26 In addition, the preparation of these controlled release systems is relatively complicated.…”
Section: Introductionmentioning
confidence: 99%
“…To further enhance chondrogenesis and address issues of phenotype inhomogeneity, MPs have been cultured within MSC pellets in order to introduce differentiation cues in a more uniform manner [Fan et al, 2008; Solorio et al, 2010; Ravindran et al, 2011; Ansboro et al, 2014]. Prior experiments have investigated the effects of poly(lactic-co-glycolic acid) (PLGA), poly(ethylene glycol) (PEG), hyaluronic acid (HA) MPs, or gelatin MPs on chondrogenesis of MSC pellets [Fan et al, 2008; Solorio et al, 2010; Ravindran et al, 2011; Ansboro et al, 2014].…”
Section: Introductionmentioning
confidence: 99%
“…Prior experiments have investigated the effects of poly(lactic-co-glycolic acid) (PLGA), poly(ethylene glycol) (PEG), hyaluronic acid (HA) MPs, or gelatin MPs on chondrogenesis of MSC pellets [Fan et al, 2008; Solorio et al, 2010; Ravindran et al, 2011; Ansboro et al, 2014]. The incorporation of gelatin [Fan et al, 2008] and PEG MPs [Ravindran et al, 2011] induced GAG and collagen II production comparable to pellets lacking MPs, while PLGA MPs promoted more homogeneous GAG deposition [Solorio et al, 2010]. In addition, PEG MPs reduced collagen I and X gene expression, which are markers of non-articular chondrocyte phenotypes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been speculated that hMSC can thrive especially well in the undifferentiated state in presence of RGD [10]. Recently, it has been investigated whether hMSCs can be pushed towards the discogenic pathway by the addition of RGD motive [13,14]. The recent study found a weaker effect of transforming and growth factor β 3 (TGFβ 3 ) [10] if RGD motive was added to an alginate culture system.…”
Section: Introductionmentioning
confidence: 99%